118k views
20 votes
How do u find the fraction result of this equation,
Im confused

How do u find the fraction result of this equation, Im confused-example-1
User Crismely
by
5.0k points

1 Answer

9 votes

At step 2, we arrive at

(2x + 3) (x + 3) = 0

and the next step (which isn't actually shown) is to use the so-called zero-product property that says if
ab=0, then
a=0 or
b=0. This means

2x + 3 = 0 or x + 3 = 0

and solving the first equation leads to the rational solution.

2x + 3 = 0

2x = -3

x = -3/2

User Justin Lucente
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.